PROTOTYPE PEMISAH PAKET BERDASARKAN WARNA OTOMATIS BERBASIS ARDUINO MEGA - Erianto Rejeki Siregar; Eva Morani Sinurat; Irenius Lumban gaol; Dian Putra Saragi; Eka Dodi Suryanto (JURNAL ILMIAH NUSANTARA, 2026)
Manual package sorting processes in industries are highly susceptible to human error, which significantly hinders production efficiency. This research aims to design and implement a prototype of an automated package sorting system based on the Arduino Uno microcontroller, utilizing color identification parameters. This system was developed to enhance the accuracy and speed of the sorting process within a production line. The research method involves integrating hardware components, including a conveyor system, Infrared (IR) sensors, a TCS3200 color sensor, a servo motor, and an LCD screen. The system's operational mechanism begins with the detection of an object by the IR sensor, which triggers a precise stop of the conveyor motor directly beneath the color sensor. The color spectrum data captured by the TCS3200 sensor is then processed by the Arduino Uno to drive the servo actuator toward the designated storage location. Test results indicate that the prototype operates with a system success rate of 90%. Based on the test data, the conveyor transport mechanism and the IR sensor's stopping system demonstrate high accuracy. However, fluctuations in color reading precision were observed, influenced by ambient light interference. In conclusion, while the system is effective for automated sorting, it requires optimization in light isolation around the sensor area to improve overall color detection reliability.